(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article analyzes the issues of language acquisition based on the behavioristic approach and its application in the language acquisition process of the visually impaired. Furthermore, the advantages, limitations, and practical application possibilities of the theory are highlighted. The views of behaviorist scholars on how the language learning process is shaped by external environmental influences, experiences, and reinforcement are presented.